Immobile crystallization of radioactive iodide by redox transformation of a low crystalline copper phase. (January 2022) - Lee, Seung Yeop; Seo, Hyo Jin; An, Ha-Rim; Kwon, Jang-Soon
Abstract: Here we show an innovative way to effectively scavenge highly mobile radioiodide and to dramatically reduce its waste volume through a spontaneous phase transformation. Under an anaerobic condition, as metallic copper (II) was favorably associated with bicarbonate (HCO3 − ) in solution, a cupriferous carbonate compound (malachite) quickly formed, which was redox-sensitive and transformable to a compact crystal of CuI (marshite). The formation of CuI crystal was principally led by the spontaneous Cu–I redox reaction centering around the copper phase over the presence of sulfate (SO4 2− ). The completely transformed CuI crystal was poorly soluble in water and grew to large microcrystals (∼μm) via a remarkable selectivity for I − . Interestingly, this redox-induced iodide crystallization was rather promoted over the existence of anionic competitors (e.g., HCO3 − and SO4 2− ), which usually exist in wastewater and natural water. Unlike the conventional methods, these competing anions positively behaved in our system by supporting that the initial malachite was more apt to be reactive to largely attract highly mobile I − . Under practical environments with various anions, such a selective I − uptake and fixation within a compact crystalline space will be a promising way to effectively remove I − in a great capacity. Graphical abstract: Image 1 Highlights: Crystallization of mobile iodide through a copper phase transformation. Environmental durable CuI (marshite) crystalline form. Sulfate can be an electron transfer agent on the Cu–I redox reaction. Selective iodide crystallization method produces a very small radioactive waste volume.